U.S. Firms on Foreign (tax) Holidays - CHOW, Travis K. (Institutional Knowledge at Singapore Management University, 2018)
We undertake the first large-sample analysis of foreign tax holiday participation by U.S. firms. Tax holidays are temporary reductions of tax granted by governments, usually contingent on the firm making new operational investments in the country. We predict and find that firms are more likely to participate in foreign tax holidays if they are highly capital-intensive and have highly profitable foreign operations, and less likely to participate in foreign tax holidays if they are capital constrained and if the firm is headed by a short-term focused CEO. While foreign tax holidays reduce taxes on foreign income, we also find that during our sample period they increase the amount of U.S. tax on foreign income. Finally, we predict and find that firms participating in foreign tax holidays increase the amount of foreign earnings that they deem to be permanently reinvested for financial reporting purposes.